Profitability of Summer BARI Hybrid Tomato Cultivation in Jessore District of Bangladesh (Journal of Agriculture & Rural Development, 2010)
The present study was conducted at Bagherpara thana under Jessore district to assess the profitability, contribution of factors to production and changes in socio-economic status of the farmers. About 42% and 21% of total variable cost was incurred for tunnel preparation and using human labour, respectively. The average yield of BARI hybrid tomato was found 32.78 t/ha. The average return per hectare over variable cost is observed to be Tk 11,44,387 on full cost basis and Tk 12,07,481 on cash cost basis. On an average benefit cost ratio was found to be 4.19 on full cost basis and 5.09 on cash cost basis. The cost per kilogram of hybrid tomato cultivation was Tk 10.94 and return from one kilogram of tomato production was Tk 45.83. The functional analysis shows that MP and TSP had positive significant contribution to yield while human labour, hormone, irrigation and seed had negative significant impact on yield of hybrid tomato. The overall socio-economic status of the sample farmers was found increased by 20.33 percent. High price of tunnel materials, timely non availability of hormone, insect and diseases attack were reportedly the major problems for tomato production. Key words: Hybrid tomato, profitability, socio-economic status. DOI: 10.3329/jard.v7i1.4424 J Agric Rural Dev 7(1&2), 73-79, June 2009